2021
DOI: 10.1021/acsnano.0c07609
|View full text |Cite
|
Sign up to set email alerts
|

Band-Order Anomaly at the γ-Al2O3/SrTiO3 Interface Drives the Electron-Mobility Boost

Abstract: Rich functionalities of transition-metal oxides and their interfaces bear an enormous technological potential. Its realization in practical devices requires, however, a significant improvement of yet relatively low electron mobility in oxide materials. Recently, a mobility boost of about two orders of magnitude has been demonstrated at the spinel/perovskite γ-Al 2 O 3 /SrTiO 3 interface compared to the paradigm perovskite/perovskite LaAlO 3 /SrTiO 3 . We explore the fundamental physics behind this phenomenon f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 58 publications
4
31
0
Order By: Relevance
“…Recently, combining theoretical and experimental results, it is found a nontrivial orbital occupation occurs in GAO/STO interface. [ 21–24 ] This novel electronic structure and the resultant interfacial reconstruction could be due to the symmetry breaking at the interface between the nonisostructural GAO and STO. As for the recorded highest mobility of GAO/STO, underlying mechanism of spatial separation between interfacial oxygen vacancies and carriers in deeper STO reduced scattering is recently proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, combining theoretical and experimental results, it is found a nontrivial orbital occupation occurs in GAO/STO interface. [ 21–24 ] This novel electronic structure and the resultant interfacial reconstruction could be due to the symmetry breaking at the interface between the nonisostructural GAO and STO. As for the recorded highest mobility of GAO/STO, underlying mechanism of spatial separation between interfacial oxygen vacancies and carriers in deeper STO reduced scattering is recently proposed.…”
Section: Introductionmentioning
confidence: 99%
“…To suppress the second compensation effect, it may be attractive to generate 2DEGs in oxide materials in which crystal field splitting causes the d xz/yz bands to lie below the d xy bands. Recent ARPES measurements suggested that such a band order inversion occurs at interfaces between STO and γ-Al 2 O 3 31 . It would be interesting to see if the same inversion could be engineered in KTO 2DEGs.…”
Section: /16mentioning
confidence: 99%
“…Identifying the electronic structure as well as the orbital configuration becomes even more interesting upon the recent finding that the high mobility 2DEG at γ-Al 2 O 3 /STO (GAO/STO) interface shows an anomaly in orbital ordering as well as a weak electron−phonon interaction (EPI) strength of the carriers. 42,43 In this paper, we identify the electronic band structure of the buried oxide interfaces by soft X-ray angle-resolved photoemission spectroscopy (ARPES) for both bare and LMObuffered a-LAO/STO. Besides a slight decrease in the k F and carrier density as well as a strong suppression in the concentration of OVs, 39 the buffered interface exhibits two significant properties: (1) an unexpected irradiation-robust band structure, which reflects the detection of FS of intrinsic interface states, and (2) a significantly reduced EPI strength, which is absent in the nonbuffered 42,43 as well as the diluted crystalline LAO/STO interfaces.…”
Section: Introductionmentioning
confidence: 99%